SAT0179 Mri Pattern of Arthritis in Sle: A Comparative Study with Rheumatoid Arthritis and Healthy Subjects. (10th June 2014) - Tani, C.; Carli, L.; Querci, F.; D'Aniello, D.; Possemato, N.; Cagnoni, M.; Delle Sedie, A.; Riente, L.; Vagnani, S.; Davide, C.; Bombardieri, S.; Mosca, M.
Abstract : Background: Arthritis in systemic lupus erythematosus (SLE) is traditionally considered mild and non erosive, however chronic pain, hand disability and deformities are frequently reported by patients with longstanding disease. Magnetic resonance imaging (MRI) has demonstrated to be more sensitive for identifying bone damage than conventional radiography and it is widely used as an outcome measure of joint damage in rheumatoid arthritis (RA) clinical trials. Objectives: In this study we aimed at describing the magnetic resonance imaging (MRI) pattern of distribution of bone marrow oedema (BME) and joint erosion in hands and wrists of patients with Systemic Lupus Erythematosus (SLE) with arthritis in comparison with Rheumatoid arthritis (RA) and healthy subjects (H). Methods: SLE patients with arthritis (n=50), patients with RA (n=22) and H (n=48) were enrolled. Every patient underwent a non dominant hand (2nd–5th metacarpophalangeal joints) and wrist MRI without contrast injection with a low- field extremity dedicated 0.2 Tesla instrument. Results: BME was observed in 2 SLE patients at hand (4%) and in 15 at wrist (13%) versus 3 (30%) and 14 (63%) RA patients. No BME was found in H. Erosions were observed at the hand in 24 SLE patients (48%), 15 RA patients (68%) and 9 H (18%); at the wrist, in 41 (82%) SLE, all RA and 47 (97%) H. The cumulative erosive burden in SLE was significantly higher than in H (p=0.002) but similar to RA patients. In SLE, erosions were more frequent at the distal side of the metacarpophalangeal joints; the II and III phalangeal basis were the most affected joints with a 20% prevalence of erosions for both. Similarly to SLE, in RA erosion were observed predominantly at the distal side of the metacarpophalangeal joints, however in comparison to SLE, RA patients showed a significantly more frequent involvement of II-IV metacarpal heads, III and V phalangeal basis. Some erosions were also detected in H in the hand and the II, III and V phalangeal basis were the most involved bones (9%, 7% and 7%, respectively).At wrist, lunate, triquetrum and capitate were the most frequently affected bones in all the three groups.By excluding the bones frequently affected also in H, in SLE the most affected sites were hamate (40%), scaphoid (38%), radius (32%) and the I metacarpal base (30%).In RA patients, scaphoid, hamate and radius were the most affected bones (in 59%, 54% and 54% respectively); trapezius and the II-III metacarpal basis were also frequently involved. With respect to SLE patients, in RA significantly more erosions were detected at the trapezius and at the II-IV metacarpal basis. Conclusions: Joint involvement in SLE can be severe with a significant tendency to develop BME and erosions, similarly to RA; this condition is not rare as previously expected. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5100